2014
DOI: 10.1080/09712119.2014.928623
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, body weight, parity and morphometric traits on litter size in prolific Black Bengal goats

Abstract: Data on some linear traits along with age, body weight (BW) at breeding, parity and previous litter size (LZ) of 1008 pregnant Black Bengal goats were analysed using one-way Analysis of Variance. Higher age, heavier BW at breeding, higher parity order resulted more (P < 0.01) chance of triplet or quadruplet births as compared to that of single birth. Larger previous LZ resulted larger (P < 0.01) LZ in subsequent kidding. Most of the linear traits were higher (P < 0.01 or P < 0.05) in goats bearing multiple foe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…The possible reason for the significant difference between breeds is attributable to breed difference (Hyder et al, 2002), as the Teddy is highly prolific whereas the Beetal is considered medium prolific. Secondly, the parity is known to have positive effects on litter size in goats (Pan et al, 2015). Consistent with the current results, Ahlawat et al (2015a) reported significant effects of breed and parity on litter size in six Indian goat breeds.…”
Section: Discussionsupporting
confidence: 90%
“…The possible reason for the significant difference between breeds is attributable to breed difference (Hyder et al, 2002), as the Teddy is highly prolific whereas the Beetal is considered medium prolific. Secondly, the parity is known to have positive effects on litter size in goats (Pan et al, 2015). Consistent with the current results, Ahlawat et al (2015a) reported significant effects of breed and parity on litter size in six Indian goat breeds.…”
Section: Discussionsupporting
confidence: 90%
“…The overall LSM ± SE for height at withers, heart girth and body length were 41.231 ± 0.121 cm, 43.902 ± 0.120 cm and 46.791 ± 0.112 cm at 6 months; 44.621 ± 0.115 cm, 48.890 ± 0.099 cm and 52.765 ± 0.090 cm at 9 months; and 50.778 ± 0.172 cm, 55.552 ± 0.170 cm and 58.392 ± 0.207 cm at 12 months of age, respectively (Table 3, 5 and 7). These findings were in accordance with the findings of Pan et al (2015) in Black Bengal goats for height at withers and heart girth, and Saikia et al (1985) in Assam Local goats for body length. However, much higher values were recorded in Sirohi goats by Dudhe et al (2015).…”
Section: Height At Withers Heart Girth and Body Lengthsupporting
confidence: 92%
“…These findings are in accordance with the findings of Pan et al . [17] in Black Bengal goats. However, much higher values were recorded in Sirohi goats for all the traits by Dudhe et al .…”
Section: Resultsmentioning
confidence: 99%